Ego-Dissolution and Psychedelics: Validation of the Ego-Dissolution Inventory (EDI) - Nour, Matthew M.; Evans, Lisa; Nutt, David; Carhart-Harris, Robin L. (Frontiers in Human Neuroscience, 2016)
Aims: The experience of a compromised sense of ‘self’, termed ego-dissolution, is a key feature of the psychedelic experience and acute psychosis. This study aimed to validate the Ego-Dissolution Inventory (EDI), a new 8-item self-report scale designed to measure ego-dissolution. Additionally, we aimed to investigate the specificity of the relationship between psychedelics and ego-dissolution. Method: Sixteen items relating to altered ego-consciousness were included in an internet questionnaire; 8 relating to the experience of ego-dissolution (comprising the EDI), and 8 relating to the antithetical experience of increased self-assuredness. Items were rated using a visual analogue scale. Participants answered the questionnaire for experiences with classical psychedelic drugs, cocaine or alcohol. They also answered the 7 questions from the Mystical Experiences Questionnaire (MEQ) relating to the experience of unity with one’s surroundings. Results: 691 participants completed the questionnaire, providing data for 1828 drug experiences (1043 psychedelics. 377 cocaine. 408 alcohol). Exploratory factor analysis demonstrated that the 8 EDI items loaded exclusively onto a single common factor, which was orthogonal to a second factor comprised of the items relating to increased self-assuredness (rho= -.110), demonstrating discriminant validity. The EDI correlated strongly with our measure of unitive experience (rho = .735), demonstrating convergent validity. EDI internal consistency was excellent (Cronbach’s alpha 0.93). Three analyses confirmed the specificity of ego-dissolution for experiences occasioned by psychedelic drugs. Firstly, EDI score correlated with drug-dose for psychedelic drugs (rho=.371), but not for cocaine (rho=.115) or alcohol (rho=-0.055). Secondly, the linear regression line relating the subjective intensity of the experience to EDI was significantly steeper for psychedelics (unstandardized B coefficient= 0.701) compared with cocaine (0.135) or alcohol (0.144). Finally, a binary support vector machine classifier identified experiences occasioned by psychedelic drugs vs. cocaine or alcohol with over 85% accuracy using ratings of ego-dissolution and ego-inflation alone. Conclusions: Our results demonstrate the psychometric structure, internal consistency and construct validity of the EDI. Moreover, we demonstrate the close relationship between ego-dissolution and the psychedelic experience. The EDI will facilitate the study of the neuronal correlates of ego-dissolution, which is relevant for psychedelic-assisted psychotherapy and our understanding of psychosis.